2002
DOI: 10.1128/aem.68.12.6405-6409.2002
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Listeria monocytogenes to Sanitizers Used in the Meat Processing Industry

Abstract: Nineteen Listeria monocytogenes strains were characterized by automated ribotyping, pulsed-field gel electrophoresis, and plasmid profiling to determine the relationship between genotype and sanitizer resistance. Isolates within a ribogroup had a consistent sensitivity or resistance phenotype except for ribogroup C isolates. All isolates with resistance phenotypes harbored two plasmids. The sensitivity of L. monocytogenes strains to quaternary ammonium compounds (QACs) was correlated with sensitivity to saniti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
56
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(58 citation statements)
references
References 20 publications
2
56
0
Order By: Relevance
“…Genome-sequencing studies have revealed additional cadmium efflux systems on plasmids pLM80 of L. monocytogenes H7858 (23) and pLI100 of Listeria innocua CLIP 11262 (9) and, in the case of L. monocytogenes strain EGDe, on the chromosome (9). Preliminary studies in our laboratory suggested that BC resistance is also mediated by a plasmid-borne efflux system (7), even though chromosomal genes involved in multidrug resistance have also been implicated in acquired resistance to this disinfectant (21,26). One may speculate that the strains characterized in the current study acquired BC resistance determinants in addition to preexisting cadmium resistance plasmids.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Genome-sequencing studies have revealed additional cadmium efflux systems on plasmids pLM80 of L. monocytogenes H7858 (23) and pLI100 of Listeria innocua CLIP 11262 (9) and, in the case of L. monocytogenes strain EGDe, on the chromosome (9). Preliminary studies in our laboratory suggested that BC resistance is also mediated by a plasmid-borne efflux system (7), even though chromosomal genes involved in multidrug resistance have also been implicated in acquired resistance to this disinfectant (21,26). One may speculate that the strains characterized in the current study acquired BC resistance determinants in addition to preexisting cadmium resistance plasmids.…”
Section: Discussionmentioning
confidence: 80%
“…To determine resistance to BC, the cell suspensions were spotted in duplicate on MuellerHinton agar (Mueller Hinton broth with 1.2% Bacto agar (Becton Dickinson and Co.), containing 10 g/ml benzalkonium chloride (Acros, New Jersey) and 2% defibrinated sheep blood (BBL, Sparks, MD). This concentration of BC (10 g/ml) was selected after evaluating the MICs for a panel of strains, including those reported to be BC resistant and BC susceptible (26), following the protocol of Soumet et al (28). Each plate contained the panel of test strains, as well as the designated positive and negative control strains.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Exposure to disinfectants commonly used in food processing plants, such as the quaternary ammonium compound benzalkonium chloride (BC), may provide selective pressures for disinfectant resistance with an accompanying increase in fitness within the processing plant environment. Several studies have investigated prevalence and mechanisms of BC resistance in L. monocytogenes (12,31,43,50). However, less is known about the behavior and response of nonpathogenic Listeria spp.…”
mentioning
confidence: 99%
“…Plasmid based BC resistance mechanisms are reported by the various studies (131,186,187 (64,116,121,156). The prevalence of the resistance to these heavy metals varies among different serotypes of L. monocytogenes (127,128,129,147,155).…”
Section: Quaternary Ammonium Compound Bezalkonium Chloride (Bc) the mentioning
confidence: 99%